DEVELOPING TASK-BASED LEARNING MODEL FOR LANGUAGE TEACHING MEDIA COURSE IN ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Angelina, Patricia (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
Language Teaching Media is one of the obligatory courses for the fifth semester students in the English Language Education Study Program of Sanata Dharma University. It provides the students with theories on language teaching media and opportunities to create innovative teaching media. This study aims to develop a learning model for Language Teaching Media course. Therefore, this study uses Research and Development method proposed by Borg Galls. There are ten steps in the Research and Development method, namely: (1) Research and Information Collecting, (2) Planning, (3) Developing Preliminary Form of Product, (4) Preliminary Field Testing, (5) Main Product Revision, (6) Main Field Testing, (7) Operational Product Revision, (8) Operational Field Testing, (9) Final Product Revision and (10) Dissemination and Implementation. Since the aim of this study is to develop the learning model for Language Teaching Media Course, only three out of ten steps of the RD model were employed, namely: Research and Information Collecting, Planning, and Developing Preliminary Form of Product. The developed learning model would be useful to enable the students to develop and utilize media to facilitate language teaching using their creativity and innovation.